Soft Tissue Coverage of the Lower Limb following Oncological Surgery - Radtke, Christine; Panzica, Martin; Dastagir, Khaled; Krettek, Christian; Vogt, Peter M. (Frontiers in Oncology, 2016)
The treatment of lower limb tumours has been shifted by advancements in adjuvant treatment protocols and microsurgical reconstruction from limb amputation to limb salvage. Standard approaches include oncological surgery by a multidisciplinary team in terms of limb sparing followed by soft tissue reconstruction and adjuvant therapy when indicated. For development of a comprehensive surgical plan, the identity of the tumour should first be determined by histology after biopsy. Then the surgical goal and comprehensive treatment concept should be developed by a multidisciplinary tumour board and combined with soft tissue reconstruction. In this article, plastic surgical reconstruction options for soft coverage of the lower extremity following oncologic surgery will be described along with five clinical cases.